MAKNA DAN STRUKTUR PAKAIAN KARNAVAL JOGJA FASHION WEEK DI YOGYAKARTA 2007-2014 (History Department, Semarang State University and Historian Society of Indonesia, 2015)
Costume exhibition show, Jogja Fashion Week Carnival, was intended to progress clothing industry, to lessen the imported clothes, and to raise the selling value of the traditional clothes in Indonesia. Throughout 2007-2014, the costume exhibition show was adequately effective to introduce the products of traditional culture becoming local characteristics to public. The research on carnival costume was made to find out the periods of the clothing style by applying art historic approach, to explain the issue of interpretation and social interaction, I used art sociological approach. The resulted conclusion was that every style of carnival costumes reflected several meanings, such as: clothing imagery, designer, and trademark. The costume structure consists of physical and non-physical ones. The physical structure was related to the issues of style, shape, and visual appearance; while the non-physical one comprised interpretation regarding the concepts of creation, social conditions, and history. The creation of carnival costumes was influenced by social condition referring to legends, fairy tales, and the myths. In addition, the designer played essential parts, i.e. creating and constructing new fashion of carnival costume in Yogyakarta. Acara pameran pakaian Karnaval Jogja Fashion Week, dimaksudkan untuk memajukan industri pakaian menekan jumlah impor pakaian asing, dan meningkatkan nilai jual kain-kain tradisi-onal di Indonesia. Sepanjang tahun 2007-2014, acara pameran pakaian cukup efektif memperkenalkan produk budaya tradisional yang menjadi ciri khas daerah kepada masyarakat. Penelitian pakaian karnaval dilakukan untuk mengetahui periodisasi gaya pakaian dengan menggunakan pendekatan sejarah seni; untuk menguraikan persoalan pemaknaan dan interaksi sosial masyarakat, digunakan pendekatan sosiologi seni. Kesimpulan yang dihasilkan adalah setiap gaya pakaian karnaval mencerminkan beberapa makna, seperti: pencitraan kain, perancang, dan merk dagang. Struktur pakaian terdiri atas fisik dan nonfisik, struktur fisik menyangkut persoalan gaya, bentuk, dan tampilan visual, sedangkan nonfisik meliputi pemaknaan yang terkait dengan konsep penciptaan, kondisi sosial, dan sejarah. Penciptaan pakaian karnaval dipengaruhi oleh kondisi sosial yang mengacu pada legenda, dongeng, dan mitos-mitos. Selain itu terdapat peran perancang yang menciptakan dan mengkreasikan bentuk baru pakaian karnaval di Yogyakarta.